Reprodução e manipulação de personagens virtuais - Vieira, Roberto Cesar Cavalcante (2012)
Many virtual reality applications and games need a large number of virtual characters. Some of these applications require, in addition to quantity, the simulation of kinship and evolution, not only of human character models but also of di erent types of animals, toon models or other creatures. Some applications also require interactions between isolated populations with well-de ned ethnic characteristics. The identi cation of similar traits between individuals of the same family is crucial to providing increased realism to many of these systems. The main di culty in these situations is to generate models automatically, in real time, which are physically similar to a given population or family. Other realistic desirable features are the automatic body variations due to epigenetic factors and the application of facial expressions as the character interacts with the environment. In those cases, the di culty lies in nding a simple mesh adaptation system for di erent creatures with big di erences in shape. In this work, the reproduction of diploid beings is mimicked to produce character models that inherit genetic characteristics from their ancestors, with the possibility to map all genes identifying the origin of each gene. Unlike morphing techniques and other existing approaches, in our method, it is possible for a genetic characteristic from an ancestor to be manifested only after a few generations. After character generation, it is possible to apply custom body variations and facial expressions to the new models. With the same adaptation system used in all methods, it is possible to generate caricatures of characters, inserting a comic atmosphere to the application. With this solution it is possible to create interactive evolution and life-simulation games, genetics educational applications, and many other possibilities.